Hemangiopericytomas grade II are not benign tumors - Zweckberger, Klaus; Jung, Carla Sabine; Müller, Wolf C.; Unterberg, Andreas; Schick, Uta (Acta neurochirurgica, 2011)
Hemangiopericytomas (HPs) of the central nervous system are rare tumors and afflicted with a high propensity of recurrences and metastases. Histopathologically, HPs correspond to differentiated (WHO grade II) and anaplastic (WHO grade III) tumors. With respect to the available literature and our own experiences, the aggressiveness, especially of differentiated grade II HPs, seems to be underestimated.